Philosophy and dogma: the end of the style and the philosophy stylization - Matos, Olgária Chain Féres (FCL-UNESP Laboratório Editorial, 2011)
This paper intends to illustrate that the style resignation on the philosophical writing and the adoption of the analytical pattern proceed from the transformations in the competence concept, replacing the Cultural or Humanist University by the Excellence or Information University, showing, hence, the failure of the political imaginary and the culture philosophical and existential role.